Development of strategies to improve communication management within virtual construction project teams - Eftekhari, Fathollah (2015)
Virtual project management emerged for reaction to the growing need for low-cost, highquality,and rapid solutions to complex organizational problems. Virtual project teams enable organizations to select the talents and expertise of employees by eliminating time and distance barriers. However, there are numerous evidences that the virtual nature create many challenges to effectively manage the communication within project teams and place a risk on project performance. Also, poor communication within virtual project teams cause projects to fail. This issue is due to the lack of study on strategies to clarify and emphasize the behaviours of the virtual project teams to deal with these barriers. The main objective of this study is to address this gap by identifying, examining and analysing the factors that influence the communication management among virtual project teams. In addition to this, the study aimed to identify factors that develop the sustain trust and prevent the misunderstanding within virtual team. The research process was conducted in two main phases. First phase consists of the qualitative study based on a semi structured interview method. A sampling frame was designed comprising two groups of academician experts in communication, and project management. Initially ten factors that influence communication management among virtual project teams were drawn from the literature. Subsequently, the factors subjected to a ranking process through interview. Finally, the degree of influences of these factors on communication management processes was assessed by experts. Mann Whitney U test and Pareto analysis were performed initially to achieve data reduction. The two most important factors (Lack of trust and Misunderstanding) were selected. In the second phase, respondents were selected from the three groups of construction contractor companies (G5-G7) in Malaysia (Klang Valley). Data was collected by questionnaire survey, participated by 98 valid respondents. Exploratory factor analysis, frequency distribution and descriptive analysis (mean, weight and standard deviation) were used as data analysis methods in this phase. Findings indicated that, lack of trust and misunderstanding are the two most critical barriers of communication management within virtual project teams. Moreover, findings revealed that Managing communication is the most vulnerable process of communication management against the barriers. Finally, two groups of factors that contribute to develop sustained trust and reducing misunderstanding among virtual project teams were identified. These factors were suggested as a project management strategy. This research has contributed to the field of project management. The first contribution of this study is the added two factors as most critical barriers for success of communication management within virtual project teams. In addition, this research has contributed to existing literature by emphasizing in factors and behaviours that affect the success of communication management within virtual project teams. It provide strategies to improve communication management within virtual project teams.